PENGARUH PEMBIMBINGAN DOSEN PENASEHAT AKADEMIK TERHADAP KEPUASAN MAHASISWA PADA PROGRAM STUDI PGSD UNIVERSITAS TRIBUANA KALABAHI TAHUN AKADEMIK 2023/ 2024 - Fanpada, Nehemia; Selly, Alboin; Sanjaya, Ferdino Wedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of academic advisor guidance on student satisfaction in the Elementary School Teacher Education (PGSD) Study Program at Tribuana Kalabahi University in the 2023/2024 academic year. This study used a quantitative approach with a survey method. The sample size was 113 students selected using a purposive sampling technique. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis used simple linear regression. The results showed that academic advisor guidance had a positive and significant effect on student satisfaction, with a significance value of 0.000 < 0.05 and a coefficient of determination of 38.4%. Descriptively, academic advisor guidance and student satisfaction were in the good category, although there were still weaknesses in the aspects of time availability and service accessibility. This study concludes that improving the quality of responsive and student-oriented academic advisory services is crucial in increasing student satisfaction.